Molecular dynamic simulation of the thermodynamic and kinetic properties of nucleotide base pair - 王宇杰;王珍;王晏莉;张文炳 (Chinese physics B, 2017)
A nucleotide base pair is the basic unit of RNA structures. Understanding the thermodynamic and kinetic properties of the closing and opening of a base pair is vital for quantitative understanding the biological functions of many RNA molecules. Due to the fast transition rate, it is difficult to directly observe opening and closing of single nucleic acid base pair in experiments. This review will provide a brief summary of the studies about the thermodynamic and kinetic properties of a base pair opening and closing by using molecular dynamic simulation methods.